Low temperature photoluminescence properties of CsPbBr3 quantum dots embedded in glasses. Issue 26 (26th June 2017) - Ai, Bing; Liu, Chao; Deng, Zhao; Wang, Jing; Han, Jianjun; Zhao, Xiujian
Abstract : Size dependence of exciton activation energy, electron–phonon coupling strength, and thermal expansion of the bandgap of CsPbBr3 QDs were studied. Abstract : The photoluminescence properties of perovskite CsPbBr3 QDs embedded in glasses were investigated at cryogenic temperature in the range of 40–240 K. CsPbBr3 QDs with radii of 3.3 nm, 4.2 nm and 4.8 nm were precipitated in phosphate glasses using conventional thermal treatment. Photoluminescence (PL) integral intensities, bandgap energies and full with at half maximum of the PL bands of CsPbBr3 QDs showed a strong dependence on temperature. An exciton binding energy of ∼40 meV was derived from the temperature-dependent emission intensity. Optical phonon energy involved in the exciton–phonon interaction was found to be ∼56 meV, about three times as that of the single phonon energy. Exciton–phonon coupling strength and the lattice thermal expansion coefficient were strongly dependent on the size of CsPbBr3 QDs, and as a result, inflection temperature of the PL peak energies of CsPbBr3 QDs increased as the size increased.